Penerapan Digitalisasi Pencatatan dan Pelaporan Keuangan untuk Meningkatkan Akuntabilitas (Studi Kasus pada KOGU Lawang) - Raditya Maulana Hasjim; Indah Dewi Nurhayati; Endah Puspitosarie (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze how digitizing financial recording and reporting systems can improve accountability, especially in the context of micro, small, and medium enterprises (MSMEs). The research was conducted at Kogu Lawang, a coffee shop that previously used manual recording methods in its financial management. The main issue faced was the lack of consistency and tracking of financial transactions, which hindered accurate and timely reporting. The method applied in this research was descriptive-qualitative, with data collection through interviews, direct observation, and documentation when the digital financial application named Akuntansiku was implemented. The selection of this application was based on its ability to meet the recording and reporting needs of SMEs, such as transaction recording, account classification, and the preparation of financial reports quickly. This application motivates entrepreneurs to be more careful in recording transactions directly, which were previously often delayed due to manual recording. Although they initially faced difficulties in adapting to the application and required internet access, this digital system is clearly more efficient and reliable than traditional methods. Overall, digitization in financial recording and reporting can be a strategic solution to improve transparency, tracking, and accountability in the MSME sector.